The dark side of energy poverty: Who is underconsuming in Spain and why?. (April 2022) - Barrella, Roberto; Romero, José Carlos; Linares, José Ignacio; Arenas, Eva; Asín, María; Centeno, Efraim
Abstract: The traditional energy poverty 'objective' metrics are mostly focused on households spending a disproportionate share of income on energy. Nevertheless, vulnerable people could also restrict their energy consumption and this 'hidden energy poverty' is not sufficiently considered in metrics and policies. This paper investigates this phenomenon and proposes a new methodology to determine an absolute threshold below which households' actual energy expenditures are too low to meet their required energy needs. Thereafter, an income criterion is introduced as a proxy to exclude households that have low energy expenditures for reasons other than lack of affordability. Finally, this article analyses the sensitivity of results to the assumptions made for the absolute energy expenditure threshold and the income threshold, thus presenting an alternative 'adjusted to reality' scenario. The results for the Spanish case study show that, in 2019, 45% of households had low absolute energy expenditures, but only 56% of these (25% of the total households) were suffering from hidden energy poverty. Besides, the average annual 'energy poverty gap' per household was €374, and the national budget needed to potentially fill this gap was €1, 692 m. Moreover, there was a broad regional disparity depending on climatology and income, and several key factors have been identified, i.e. household size, housing's energy efficiency and tenure, and locality's degree of urbanisation. Thus, the macro-level analysis carried out in this paper makes it possible to characterise hidden energy poverty in Spain, and the policy recommendations provided might guide policymakers to target assistance programs more effectively.